Les négociations de sens dans un dispositif d'apprentissage des langues en ligne synchrone par visioconférence - Viorica Nicolaev (Recherches en didactique des langues et des cultures)
The aim of this article is to determine how videoconferencing-supported interaction in distance language learning may promote the acquisition of an L2. The context of this research is the program "Français en 1ère ligne" which brings together teachers in training and American learners of French via a desktop platform.We analyze three tasks carried out by five pairs of learners from an interactional and acquisitional perspective. Results from this research show that instances of negotiation of meaning occurred in videoconferencing-supported interaction in a similar way to those reported in the classroom. The study also indicates that the videoconferencing-supported environment has an impact on the structure and the nature of negotiation of meaning.